2014
DOI: 10.1016/j.watres.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical fate of solvent constituents of Corexit oil dispersants

Abstract: In 2010, an estimated 1.87 million gallons (7079 cubic meters) of chemical dispersants were applied to open ocean waters in the Gulf of Mexico as part of the response to the Deepwater Horizon blowout. This unprecedented volume of dispersant application highlighted the importance of dispersant chemical formulations, raising questions of dispersant fate and transport in the open ocean and spurring research into formulation improvements. The research presented here elucidates the contribution of photolytic proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Thus, the surfactant alkyl and acyl side chains might have been degraded by the detected AlkB1 homologue, cytochrome P450 hydroxylase, or lipases, while the proteins related to sulfur metabolism detected in Corexit treatments might have been involved in DOSS metabolism. Moreover, the solvent fraction of Corexit reportedly contains propylene glycol and dipropylene glycol monobutyl ether [81], which could also have been degraded by strain TT1 as shown for other isolates [18]. In order to establish a better connection of these potential substrates to the observed proteomic response of strain TT1, further experimental studies using only specific surfactants or glycols as carbon substrates are required.…”
Section: Metabolism Of Other Corexit Componentsmentioning
confidence: 99%
“…Thus, the surfactant alkyl and acyl side chains might have been degraded by the detected AlkB1 homologue, cytochrome P450 hydroxylase, or lipases, while the proteins related to sulfur metabolism detected in Corexit treatments might have been involved in DOSS metabolism. Moreover, the solvent fraction of Corexit reportedly contains propylene glycol and dipropylene glycol monobutyl ether [81], which could also have been degraded by strain TT1 as shown for other isolates [18]. In order to establish a better connection of these potential substrates to the observed proteomic response of strain TT1, further experimental studies using only specific surfactants or glycols as carbon substrates are required.…”
Section: Metabolism Of Other Corexit Componentsmentioning
confidence: 99%
“…A second factor that might affect dispersant effectiveness is the solvent compatibility between the co-solvent system of the dispersant and the oil residues . We tested solvent compatibility of our oil residues with two types of co-solvent that are known to be present in Corexit 9500: two different hydrotreated light petroleum distillates and dipropylene glycol n -butyl ether (DPnB). DPnB has been used as a marker compound for Corexit during the Deepwater Horizon oil spill. We found that oil residues irradiated for 4–11 days had a reduced solubility in the petroleum distillates (average solubility: 68 ± 13%); in contrast, DPnB, as well as 1:1 mixtures of DPnB and petroleum distillates, was able to completely dissolve irradiated oil residues (Figure S10). To test whether the decreased solubility of irradiated oil residues in petroleum distillates could explain the measured reduction in dispersant effectiveness, we pre-mixed Corexit 9500A with the photo-oxidized residue L8 prior to the Baffled Flask Test.…”
Section: Resultsmentioning
confidence: 99%
“…The degree to which oil products are significant sources of organic carbon is not clear and transformations of oil products in salt marshes are poorly characterized. While a number of literature studies aim to understand the photo and biodegradation of oil compounds in marine environments associated with oil spills (Bugden et al, 2008;Islam et al, 2013;King et al, 2014;Kover et al, 2014), little is known about oil seeps and oil transformations in salt marshes. Understanding the contribution of oil to the DOM pool in salt marshes is important in evaluating the short and long term influence of oil pollution on coastal ecosystems and intertidal water chemistry (McClenachan et al, 2013;Wang et al, 2013;Marton and Roberts, 2014).…”
Section: Introductionmentioning
confidence: 99%